Eukaryotic replication origins: Strength in flexibility. (3rd May 2016) - Kumar, Charanya; Remus, Dirk
ABSTRACT: The eukaryotic replicative DNA helicase, Mcm2-7, is loaded in inactive form as a double hexameric complex around double-stranded DNA. To ensure that replication origins fire no more than once per S phase, activation of the Mcm2-7 helicase is temporally separated from Mcm2-7 loading in the cell cycle. This 2-step mechanism requires that inactive Mcm2-7 complexes be maintained for variable periods of time in a topologically bound state on chromatin, which may create a steric obstacle to other DNA transactions. We have recently found in the budding yeast, Saccharomyces cerevisiae, that Mcm2-7 double hexamers can respond to collisions with transcription complexes by sliding along the DNA template. Importantly, Mcm2-7 double hexamers remain functional after displacement along DNA and support replication initiation from sites distal to the origin. These results reveal a novel mechanism to specify eukaryotic replication origin sites and to maintain replication origin competence without the need for Mcm2-7 reloading.